Determination and correlation of solubility and thermodynamic properties of pyraclostrobin in pure and binary solvents. (October 2016) - Yang, Peng; Du, Shichao; Qin, Yujia; Zhao, Kaifei; Li, Kangli; Hou, Baohong; Gong, Junbo
Highlights: The solubility data of pyraclostrobin in pure and binary solvents were determined and correlated. The theory of solubility parameter was used to explain the cosolvency in binary solvents. A modified mixing rule was proposed to calculate the solubility parameter of binary solvents. The dissolution thermodynamic properties were calculated and discussed. Abstract: The solubility of pyraclostrobin in five pure solvents and two binary solvent mixtures was measured from 283.15 K to 308.15 K using a static analytical method. Solubility in five pure solvents was well correlated by the modified Apelblat equation and Wilson model. While the CNIBS/R–K model was applied to correlate the solubility in two binary solvent mixtures, the correlation showed good agreement with experimental results. The solubility of pyraclostrobin reaches its maximum value at a certain cyclohexane mole fraction in the two binary solvent mixtures. The solubility parameter of pyraclostrobin was calculated by the Fedors method and a new modified mixing rule with preferable applicability was proposed to determine the solubility parameter of solvents. Then the co-solvency in the binary solvent mixtures can be explained based on the obtained solubility parameters. In a addition, the dissolution thermodynamic properties were calculated from the experimental values using the Wilson model.